2015
DOI: 10.1007/s12011-015-0300-0
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a Low Lead Concentration Impairs Contractile Machinery in Rat Cardiac Muscle

Abstract: Lead exposure has been considered to be a risk factor for hypertension and cardiovascular disease. Our purpose was to evaluate the effects of low plasma lead concentration on cardiac contractility in isolated papillary muscles. Wistar rats were divided in control group or group treated with 100 ppm of lead acetate in the drinking water for 15 days. Blood pressure (BP) was measured weekly. At the end of the treatment period, the animals were anesthetized and euthanized, and parameters related to isolated papill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…7 Epidemiology studies indicated that exposure to even low levels of Pb was associated with an increased incidence of clinical cardiovascular end points such as hypertension, arteriosclerosis, coronary heart disease, and stroke. 8,9 Pb could deposit abnormally on the arterial wall and heart valve and cause constructional and functional transformation of cardiovascular system. 10 Yet, there is no clear evidence to indicate whether co-exposure to SiNPs and Pb could lead to cardiovascular toxicity in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…7 Epidemiology studies indicated that exposure to even low levels of Pb was associated with an increased incidence of clinical cardiovascular end points such as hypertension, arteriosclerosis, coronary heart disease, and stroke. 8,9 Pb could deposit abnormally on the arterial wall and heart valve and cause constructional and functional transformation of cardiovascular system. 10 Yet, there is no clear evidence to indicate whether co-exposure to SiNPs and Pb could lead to cardiovascular toxicity in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…As such, these channels and transporters are likely targets during lead poisoning. Moreover, there are some clinical reports about heart effects seen during lead poisoning, but there are only a few studies that have attempted to understand the effects of lead exposure in the heart at the molecular level (Basha et al 2012;Bhatnagar 2006;Kurppa et al 1984;Missiaen et al 2000;Scoote and Williams 2004;Silva et al 2015;Taylor 1996;Tollestrup et al 1995;Williams et al 1983). In this paper, we study the effects of Pb 2+ on contractility, heart rate and arrhythmias in isolated heart cells from guinea pigs and mice.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, these findings possess immediate meaning and significance for public health around the world (Silva et al, 2015). Although environmental and occupational exposure to lead has declined in the past decades in Europe (Pawlas et al, 2013;Hrubá et al, 2012), the risk for damage to cardiovascular functions by short-term or low-concentration lead exposure should not be underestimated.…”
Section: Effects Of Low Lead Exposure On Cardiovascular Diseasementioning
confidence: 97%
“…Nevertheless, many recent studies found that low levels of lead exposure, even below the threshold considered safe, could bring about potential harm and detrimental effects to cardiovascular systems (Silva et al, 2015;Fiorim et al, 2011), which posed a challenge to the established safe threshold as well as a caution for the world on the ubiquitous low levels of lead exposure. The safe threshold has varied dramatically, constantly going lower and lower over the past.…”
Section: Effects Of Low Lead Exposure On Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation